The Influence of Work-Life Balance and Work Discipline on Employee Performance at Aston Batam Hotel and Residence - Fajri Adrizal; Khairani Saladin (Pt. Threeple Herphi Educate, 2025)
This study examines the effects of work-life balance and work discipline on employee performance at a four-star hotel in Batam, Indonesia, using a quantitative causal-associative design with purposive sampling of 112 employees from a population of 156. Data were collected through a structured questionnaire adapted from validated hospitality and organizational behavior measures, analyzed using IBM SPSS Statistics 26.0 with validity testing via Pearson’s correlation, reliability via Cronbach’s alpha (≥ 0.70), and classical assumption tests including Kolmogorov–Smirnov, Variance Inflation Factor, and Glejser methods, followed by multiple linear regression analysis. Results show that both work-life balance (β = 0.657, p < 0.001) and work discipline (β = 0.309, p = 0.002) have positive and significant effects on performance, jointly explaining 53.3% of its variance (Adjusted R² = 0.533, F = 62.835, p < 0.001), with work-life balance exerting a stronger influence. These findings highlight the importance for hospitality managers in emerging tourism destinations to integrate employee well-being initiatives, such as flexible scheduling and wellness programs, with strict adherence to service standards and operational discipline, thereby contributing to the hospitality human resource management literature by providing empirical evidence from a rapidly developing tourism hub in Indonesia.